Analisis Perbandingan Persepsi Masyarakat Terhadap Bank Syariah dan Bank Konvensional (Survei Pada Masyarakat Telaga Murni RT.001 RW.005 Kecamatan Cikarang Barat Kabupaten Bekasi) - Adie Septiana, M Rifky; Putra, Purnama (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
This study analyzes the comparison of people's perceptions of Islamic Banks and ConventionalBanks.This research is a qualitative research based on the philosophy of postpositivism, used toexamine natural conditions, as opposed to an experiment where the researcher is the key instrument,the data collection technique is carried out in a combination of inductive or qualitative triangulationanalysis, and the results of qualitative research emphasize the meaning. than generalizations. Throughqualitative research, the author explains and describes the comparison of people's perceptions aboutIslamic banks and conventional banks as they are based on data and facts obtained at the time of theresearch. Researchers can also analyze to find out the meaning and implications of the problem understudy, namely a comparative analysis of public perceptions about Islamic banks and conventionalbanks in Telaga Murni Housing Rt.001 Rw.005 Cikarang Barat District Bekasi Regency. Based on theresults of interview research regarding public perceptions of Islamic banks and conventional banks,of the 10 respondents, there were 9 who were considered good and understood and used Islamicbanking services and 1 respondent was considered quite good and understood Islamic banks. Thereare 10 respondents who are considered good, understand and use conventional bank services, andare familiar with conventional banks. Meanwhile, 1 respondent did not yet have an account at anIslamic bank and a conventional bank, but the respondent knew and understood Islamic banks andconventional banks.